Acute Haemarthrosis in the Haemophilia A Rat Generates a Local and Systemic Proinflammatory Response - Lövgren, Karin M.; Christensen, Kristine R.; Majewski, Wiktor; Østrup, Olga; Skov, Søren; Wiinberg, Bo (Thrombosis and Haemostasis, 2017)
Background Replacement therapy with coagulation factor VIII (FVIII) concurrent with bleeds (on-demand) in haemophilia A (HA) patients has been hypothesized to increase the risk for antidrug antibodies (inhibitors). A danger signal environment, characterized by tissue damage and inflammation at the site of a bleed, is thought to contribute to the anti-FVIII response. The nature of this inflammatory reaction is, however, not fully known, and new insights will be valuable for both managing inhibitors and understanding arthropathy development.Objective To characterize the inflammatory response, locally and systemically, during the first 24 hours following a joint bleed in the HA rat.Methods HA rats received a needle-induced knee joint bleed (n = 83) or a sham procedure (n = 41). Blood samples were collected at selected time points from 0 to 24 hours post injury/sham. Synovial fluid, intra-articular knee tissue and popliteal lymph nodes were collected at 24 hours. Cytokine/chemokine concentrations and gene expression were measured.Results Gene expression analysis revealed a rapid inflammatory response in the injured knees, accompanied by significantly increased levels of specific gene products in the synovial fluid; IL-1β, TNFα, KC/GRO, IL-6, Eotaxin, MCP-1, MCP-3, MIP-1α, MIP-2, RANTES, A2M and AGP. Plasma analysis demonstrated significantly increased systemic levels of KC/GRO and IL-6 in injured rats already after 5 to 6 hours.Conclusion A rapid proinflammatory response, locally and systemically, characteristic of innate immunity, was demonstrated. Results reveal a more comprehensive inflammatory picture than previously shown, with resemblance to human haemophilic arthropathy, and with unique correlation between gene expression level, synovial concentration and plasma concentration in individual rats.
Keywords: gene expression; haemarthrosis; haemophilia A; inflammation; rat